The Evaluation of Potential Usage of Ti4N3Tx MXene as Interface Layer Catalyst of Bipolar Membrane - Celik, Aytekin; Aksoy, Yunus; Hanay, Ozge; Halisdemir, Umay; Hasar, Halil (Springer, 2025)
Modifications to the membrane and interface layer are crucial for enhancing bipolar membrane (BPM) performance. This study investigates the potential use of Ti4N3Tx in the BPM interface layer. Ti4N3Tx was synthesized from the Ti4AlN3 MAX phase via salt melting, and its successful synthesis was confirmed through X-ray diffraction, X-ray photoelectron spectroscopy, thermogravimetric analysis, atomic force microscopy, and water contact angle analyses. Incorporating Ti4N3Tx significantly increased BPM hydrophilicity. The water uptake capacity of BPM-1/PS (without Ti4N3Tx) and BPM-3/PS (containing 0.4 wt% Ti4N3Tx in polymer suspensions) was 10% and 17%, respectively. The Young's modulus of BPM-1/PS was 634 MPa, whereas BPM-2/PS (with 0.2 wt% Ti4N3Tx in polymer suspension) exhibited 963 MPa, enhancing BPM stability. However, increasing the MXene content raised electrical resistance from 0.26 Omega center dot cm(2) (BPM-1/PS) to 2.00 Omega center dot cm(2). Compared to conventional BPM interface materials, such as metal oxides and carbon-based nanomaterials, Ti4N3Tx MXene offers a unique combination of tunable hydrophilicity, mechanical reinforcement, and surface charge modulation, providing an alternative strategy for optimizing BPM performance. These findings suggest that MXene-modified BPMs are promising for electrochemical water splitting, electrodialysis, and redox flow batteries, as well as wastewater treatment and energy storage applications.
Keywords: Bipolar Membrane; MXene; Interface Layer; Ti4N3TX